2021
DOI: 10.1186/s13018-021-02671-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of ultra-early rehabilitation on elbow function after Slongo’s external fixation for supracondylar humeral fractures in older children and adolescents

Abstract: Objective To evaluate the efficacy of ultra-early rehabilitation on elbow function after Slongo’s external fixation for supracondylar humeral fractures in older children and adolescents. Methods We retrospectively analyzed clinical data from 49 older children (> 8 years) and adolescents with supracondylar humerus fracture who were treated with Slongo’s external fixation in our hospital from January 2016 to August 2020. Twenty-three patients rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 24 publications
(24 reference statements)
0
11
0
Order By: Relevance
“…Golden et al [3] reported a correlation between increased BMI and reduced range of movement (ROM) of the elbow, with an expected loss of ROM of about 11° to 17° for obese children because of a soft tissue block to full flexion. Therefore, He et al [1] should have measured reduced flexion and total ROM of the un-injured arm for the obese R-group compared to the C-group but reported equal mean values instead, which would be highly unlikely considering Golden et al 's data [3].…”
mentioning
confidence: 96%
See 4 more Smart Citations
“…Golden et al [3] reported a correlation between increased BMI and reduced range of movement (ROM) of the elbow, with an expected loss of ROM of about 11° to 17° for obese children because of a soft tissue block to full flexion. Therefore, He et al [1] should have measured reduced flexion and total ROM of the un-injured arm for the obese R-group compared to the C-group but reported equal mean values instead, which would be highly unlikely considering Golden et al 's data [3].…”
mentioning
confidence: 96%
“…We read with interest the recent publication by He and colleagues [1]. The authors [1] stated that the time to regain the range of movement required for functional activity of daily living (ROM-ADL: flexion = 30°-130°; forearm rotation = 100° (50° pronation, 50° supination)) [2] was significantly shorter for the rehabilitation group (R-group) than the control group (C-group), but this is contradicted by the provided data listed in the authors' first table (time to ROM-ADL: C-group = 6.65 ± 0.8 weeks; R-group = 9.74 ± 1.25 weeks).…”
mentioning
confidence: 99%
See 3 more Smart Citations